ОРФОЛОГІЧНІ ХАРАКТЕРИС ТИКИ ПЕРШОГО ПОЛЯРНОГО ТІЛА ООЦИТІВ ЛЮДИНИ ТА РЕЗУЛЬТАТИ PGT-A ЕМБРІОНІВ - Юрчук, Таїсія; Будерацька, Наталія; Ільїн, Ігор; Гонтар, Юлія; Петрушко, Марина (Morphologia, 2019)
ABSTRACT. Background. The relevance of studying problem of oogenesis is due to the high rate of infertile marriages associated with problems in the reproductive sphere. Human oocytes at meiosis metaphase II are characterized by polymor phism of the first polar body, which morphological features can be a predictor of the embryos chromosomal status. Objec tive. Determination of chromosomal status of embryos derived from oocytes with different morphological characteristics of the first polar body. Methods. Preimplantation-genetic analysis of embryos was performed using molecular cytogenetic methods; culturing method was used to fertilised oocyte and development of preimplantation embryo, assessment of oocyte and embryo development were studied by the light and fluorescence microscopy; cryobiological and statistical methods were also used. Results. It has been shown that the oocyte fertilization rate does not dependent on the first polar body morphology. However, oocytes with an enlarged and scattered-fragmented polar body do not develop after fertilization until blastocyst stage. That is why it impossible to carry out their genetic analysis. Ferltilisation of the oocytes with local fragmentation of the polar body does not increase the incidence of embryo aneuploidy. Conclusion. The morphological characteristics of the first polar body may indirectly indicate the chromosomal status of human embryos. The data obtained will facilitate the selection of eggs for patients undergoing ART treatment in cases where the creation of an excessive number of embryos should be avoided. Key words: oocyte, polar body, genetic testing, euploid chromosome set.
Keywords: oocyte; polar body; genetic testing; euploid chromosome set.